Clinical importance of respiratory muscle fatigue in patients with cardiovascular disease. Issue 34 (21st August 2020) - Taya, Masanobu; Amiya, Eisuke; Hatano, Masaru; Saito, Akihito; Nitta, Daisuke; Maki, Hisataka; Hosoya, Yumiko; Minatsuki, Shun; Tsuji, Masaki; Sato, Tatsuyuki; Murakami, Haruka; Narita, Koichi; et al.
Abstract : Abstract: Patients with cardiovascular diseases frequently experience exertional dyspnea. However, the relationship between respiratory muscle strength including its fatigue and cardiovascular dysfunctions remains to be clarified. The maximal inspiratory pressure/maximal expiratory pressure (MIP/MEP) before and after cardiopulmonary exercise testing (CPX) in 44 patients with heart failure and ischemic heart disease were measured. Respiratory muscle fatigue was evaluated by calculating MIP (MIPpost/MIPpre) and MEP (MEPpost/MEPpre) changes. The mean MIPpre and MEPpre values were 67.5 ± 29.0 and 61.6 ± 23.8 cm H2 O, respectively. After CPX, MIP decreased in 25 patients, and MEP decreased in 22 patients. We evaluated the correlation relationship between respiratory muscle function including respiratory muscle fatigue and exercise capacity evaluated by CPX such as peak VO2 and VE/VCO2 slope. Among MIP, MEP, change in MIP, and change in MEP, only the value of change in MIP had an association with the value of VE/VCO2 slope (R = −0.36, P  = .017). In addition, multivariate analysis for determining factor of change in MIP revealed that the association between the change in MIP and eGFR was independent from other confounding parameters (beta, 0.40, P  = .017). The patients were divided into 2 groups, with (MIP change < 0.9) and without respiratory muscle fatigue (MIP change > 0.9), and a significant difference in peak VO2 (14.2 ± 3.4 [with fatigue] vs 17.4 ± 4.7 [without fatigue] mL/kg/min; P  = .020) was observed between the groups. Respiratory muscle fatigue demonstrated by the change of MIP before and after CPX significantly correlated with exercise capacity and renal function in patients with cardiovascular disease. Abstract : Supplemental Digital Content is available in the text